8(h+2)-5(h-1)=6h

Simple and best practice solution for 8(h+2)-5(h-1)=6h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(h+2)-5(h-1)=6h equation:


Simplifying
8(h + 2) + -5(h + -1) = 6h

Reorder the terms:
8(2 + h) + -5(h + -1) = 6h
(2 * 8 + h * 8) + -5(h + -1) = 6h
(16 + 8h) + -5(h + -1) = 6h

Reorder the terms:
16 + 8h + -5(-1 + h) = 6h
16 + 8h + (-1 * -5 + h * -5) = 6h
16 + 8h + (5 + -5h) = 6h

Reorder the terms:
16 + 5 + 8h + -5h = 6h

Combine like terms: 16 + 5 = 21
21 + 8h + -5h = 6h

Combine like terms: 8h + -5h = 3h
21 + 3h = 6h

Solving
21 + 3h = 6h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6h' to each side of the equation.
21 + 3h + -6h = 6h + -6h

Combine like terms: 3h + -6h = -3h
21 + -3h = 6h + -6h

Combine like terms: 6h + -6h = 0
21 + -3h = 0

Add '-21' to each side of the equation.
21 + -21 + -3h = 0 + -21

Combine like terms: 21 + -21 = 0
0 + -3h = 0 + -21
-3h = 0 + -21

Combine like terms: 0 + -21 = -21
-3h = -21

Divide each side by '-3'.
h = 7

Simplifying
h = 7

See similar equations:

| 2x^2+40x+180=0 | | 5y+2y(y-6)=4(y+1)-2 | | X+3/4x=84 | | 10x-41=69 | | 9t-16r=-49 | | 2x^3-40x+192xy^2=0 | | x^2-2*435*x+(2*11.637*(10^6))/(0.9*0.85*20.7*800)=0 | | x^2-2*435*x+2*11.637*10^6/0.9*0.85*20.7*800=0 | | x^2-2*435*x+2*11.637/0.9*0.85*20.7*800=0 | | -4*5-4y=16 | | -3(2x+1)=x+9 | | 9*3+9y=81 | | 2(k+2)+6(k-2)=5k-2 | | .5t+15=-10 | | (7x-3)(12x-7)= | | -(2x+3)=3x+1 | | (3x-5)=2.5x+3(x-6) | | 1-10/13 | | 2x/5=5x+2/6 | | 4g-5-3-4g= | | 5n+34=-21 | | 4u=5(u-1)-3 | | 5*6*7/8 | | (2x)/5=(5x+2)/6 | | 9/3*6*4/9 | | .5x^2+.5x-6=y | | y=10/9*5+10 | | 9/3(6*4/9) | | -10z-5=-20z+1.6 | | y=10/9*4+10 | | 5x+4(-3x-5)=-22-5x | | 5-2b=3b-7b+25 |

Equations solver categories